Project Based Learning Assisted by E-Worksheet Effect on Creative Thinking Ability on Renewable Energy Topic - Tantinta, Sofiyah; Irwan Koto; Andik Purwanto; Netriani Veminsyah Ahda (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2025)
The study aims to determine the effect of physics learning using the Project Based Learning (PjBL) model assisted by E-LKPD based on Live Worksheet on the creative thinking ability of grade X students and how much influence physics learning with project-based learning model assisted by E-LKPD based on live worksheet on the creative thinking ability of grade X students. The research was conducted with a quasi-experiment design involving experimental and control classes. The results showed the average posttest of the experimental class of 66 was higher than the control class of 64.85. The Independent Sample t-Test test resulted in a t value of 4.745 and Sig. (2-tailed) < 0.001, indicating a significant difference in science understanding. Students' creative thinking skills also improved significantly with a t value of 4.745 and Sig. (2-tailed) < 0.001. The result of the effect size is 1.05, which shows that there is a significant increase in the creative thinking skills of students who use the PjBL model assisted by E-LKPD based on Live Worksheet, with the average posttest value of the experimental class higher than the control class. The application of the PjBL model involving E-LKPD based on live worksheets is proven to be effective in increasing student creativity.